The (Mis)utilization of Cues During Deception Detection in 911 Homicide Calls - Markey, Patrick (Homicide studies, 2025)
The current study explored cue utilization during 911 homicide calls to better understand deception detection in this high-risk situation. A sample of 93 participants judged the deceptiveness of a random subset of 110 homicide calls placed to 911. A separate group of raters coded 86 different cues expressed by each 911 caller. Results indicated that judges were unable to detect deception accurately. While judges appeared to utilize some cues correctly when assessing callers’ deception, subsequent analyses found that judges likely had difficulty detecting deception because they failed to utilize emotionally related cues correctly.